KEJENUHAN DI KALANGAN GURU BIMBINGAN DAN KONSELING DI SMAN PROVINSI RIAU - Riswani Riswani (Educational Guidance and Counseling Development Journal, 2018)
Guidance and Counseling teachers always required understanding the conditions and situation of students with a vengeance and so that required intense emotional involvement. Intense emotional involvement can lead to job stress and stress is ignored if the condition will potentially lead to burnout in the works. This study tries to find out the burnout of the picture and the factors that affect the burnout of the BK teachers, 23 respondents who have a lot of student guidance. Determination of the respondents using the technique of "snowball". The method used is a qualitative method with the phenomenological approach. Data collection techniques using in-depth interviews. The credibility of the research done by triangulation of the data sources. Based on the results of the study concluded that depersonalization, emotional exhaustion, and unwillingness in the achievement experienced by BK teachers. The Free school system, the weak role of the leader, the conditions are not the conducive working environment, workload, unclear professional status, educational qualifications, moral crisis of the students, the indifference of parents, lack of social support coworkers lead to burnout at BK teachers. Spirituality becomes a reference in the BK teachers cope with stress and burnout experienced. So the central phenomenon in this study is the burnout as a result of the stress experienced by BK teachers.